CODESRIA Bulletin Online, No. 8, July 2023 - African Feminist Epistemic Communities - Okech, Awino (CODESRIA Bulletin, 2023)
Keynote Address Presented at the Reflections Meeting on the CODESRIA Gender Institutes: Pasts and Futures Kampala, Uganda, 7 June 2023 This paper was given as a keynote address at a convening for one of CODESRIA’s flagship institutes—the gender institute. The CODESRIA gender institutes have been running for twenty-eight years, with 428 direct beneficiaries. My engagement with CODESRIA gender institutes has occurred across three different periods and different thematic areas. In 2013, I served as a resource person for African Sexualities: Theories, Politics and Action, which was co-directed by Professors Tamale and Bennett. In 2018, I was a resource person for Feminist Scholarship, Universities and Social Transformation in Africa, directed by Professor Philomena Okeke-Ihejirika. In 2021, I directed a virtual gender institute during Covid-19 on Women and Girls in Contexts of Shrinking Civic Space. As a resource person and a director who sets the intellectual tone and coherence of the institutes, I offer two reflection points. The first is on methodology—the institute and its accompanying methods, which are training, research and publications. The second reflection point focuses on the intellectual imperatives for gender institutes that take feminist theories and approaches as a foundational starting point from which to frame intellectual encounters. The continental, transnational and transdisciplinary imperatives of this work are laid out below. On The Institute as Methodology Research and training as method The gender institute proceeds on the basis that an intensive model of knowledge transfer, anchored on two weeks of robust engagement with scholarship through lectures, peer review and discussion of research papers, will collectively begin a process of introducing, re-introducing and strengthening feminist scholarship. Accompanying these two (occasionally three or four) weeks of intensive learning is the idea that a post-institute publication will offer a framework for illustrating and advancing knowledge transfer and learning. In addition, the process of working on a publication within a community of peers should strengthen the cohort and extend an epistemic community. If this methodological orientation is taken as true, then it is important to formally assess whether the body of work that has been developed across the institutes over twenty-eight years has expanded the discursive terrain on various themes. It is here that the question of CODESRIA’s role in building, sustaining and nurturing feminist epistemic communities lies because it requires an examination of the demands placed on institute participants to advance knowledge while recognising that the teaching space is often filled with ephemerality. There are multiple ways of tracking knowledge transfer. One is tracking the substantive approach to citation of feminist scholarship across publications developed from the institutes. The second is cross-citation of feminist scholarship generated through reading lists created for the institute and used by adjacent institutes, such as the governance institute. Third, would be to examine who downloads open access books and journals. The last is conducting a tracing study with institute participants to reflect on the long-term impact of the experience in their journey as intellectuals and academics. Language and intellectual genealogies CODESRIA has attempted to resolve as far as is possible the colonial legacies of the European language divide, which is often understood through anglophone, francophone, lusophone and arabophone descriptors. CODESRIA language-divide disruption efforts are seen in the reduction of the domination of English—in the choice of resource persons, access to interpretation and the diversity of successful applicants. The question of language justice across Africa is broader than the Council, which means that translation and interpretation efforts, while important, will not resolve this conundrum. Yet, there is a second challenge, which sits at the nexus of language and intellectual genealogies. I have always been struck during my engagements in the gender institutes by the vast differences in who we read and know based on our colonial histories and how these have been sustained by our education systems. What we read or do not read means that we are speaking and writing in very different intellectual languages. For feminist scholarship that also means a Eurocentricity that reproduces Africa through the white gaze, on the one hand, and scholarship that is uninterested in Africa unless it is connected to foreign policy interests, on the other hand. We can think here of the vast amount of Euro-American scholarship on the Sahel that is focused on violent extremism, anti-terrorism and militarisation, or the ‘African studies’ field. In addition, the dominance of English-language scholarship has cultivated an environment in which scholarship from the global South is under engaged—it is not cited in any substantive way that illustrates a full engagement with the scholarship. Herein lies the impact of scholarship in the world, how it travels and the geopolitical economies that shape knowledge production and transfer. Closely connected to this knowledge industry is the question of access. In reviewing and engaging with research papers, I am often struck by the age of the literature and theoretical frameworks being used where debates have developed significantly. This observation is obviously linked to the decay of public universities across Africa[1] that is partly a legacy of the structural adjustments of the 1990s, which demanded state divestment in higher education as part of donor conditionalities imposed by the World Bank and the International Monetary Fund. These donor conditionalities wreaked untold havoc on public universities and sustained a political economy of knowledge that consistently places academics in Africa on the backfoot. While there is a growing movement that pushes for open access publishing[2] as part of democratising knowledge, we must also look at the academic publishing model that generates significant income from academic publishing without any of those resources being redistributed to universities and the academics who are central to sustaining them. The academic publishing economic model as we know it has contributed to the development of established and respected journals across different disciplines. The notion of ‘respected’, often accompanied by impact factors, is a legacy of a fair amount of gatekeeping framed by ‘rigour and scientific standards’. Yet, these scientific mechanisms as secured by the peer-review systems of established journals[3] have over the last decade come under significant scrutiny for unethical practices, which include publishing research that can be considered methodologically dubious.[4] The specificity of feminist scholarship in the context I describe above lies in a global environment in which there are increasingly deliberate attacks on feminist scholarship.[5] The marginalisation of feminist scholarship, and scholarship by women[6] specifically, is well researched. In resolving the issue of access to scholarship, the ideological and political question around the choices made about what to read, what we refuse to read and why there is resistance to substantively engaging with feminist theorising remains. In my view, at the heart of the erasure of feminist scholarship is the challenge it poses to how we understand power and our location in those constellations of power. This leads me to my last point about naming what undergirds the CODESRIA gender institute as feminist thinking. Gender or Feminisms? Gender is not the study of what is evident, it is an analysis of how what is evident came to be. Maya Mikdashi, 2012[7] I have always been intrigued by who applies for the gender institute, who makes the cut and what they imagine they are going to learn from a gender institute. The traces of expectations and assumptions about the gender institute are found in the participants’ research proposals, which institute directors receive in advance. Therein you begin to see the questions that preoccupy people and the avenues along which they think through these questions. Two main traces can be seen. The first trace is in citations or the lack thereof of established African feminist voices in various fields. The second trace is a focus on the woman question in which the personhood of women is central. The research projects often focus on an interpretation of patriarchy that does not move beyond an articulation of male and female (biology) and instead solidifies the power and/or powerlessness embedded in those binaries as the site from which to define the research problems and make meaning. To offer this observation is not to ignore the material realities that structure our very gendered societies. Rather, it invites us to think about the liberation potential that is missed in the expansive interpretation of gender that foundational African feminist scholarship[8] has offered to us through which to re-interpret and re-organise power. Consequently, to deliberately foreground the gender institute as informed by feminist theories is to focus people on the theoretical and methodological anchors that will shape any discussion on gender. Let me offer an example. At SOAS, University of London, the economics department makes it very clear that its teaching and research is predominantly heterodox economics. It foregrounds the theoretical orientation of its programmes as a way of signalling to students what they will encounter in their classrooms. In effect, no students arriving at SOAS can argue that the department has not delivered neoclassical economics because that was never what it intended to do. I argue that the debate about gender and feminism in the CODESRIA gender institutes is the same. In boldly stating that the gender institutes are grounded in feminist thinking, we in effect clarify from the onset what people should expect in coming to a gender institute. Feminisms are the container for the language and analytical tools that use gender as a framework for organising power across our societies. In essence, there is no gender as an analytical category with all its varied limitations without feminisms. There are two challenges for CODESRIA. The first is that in an environment characterised by a scarcity of academic resources, the institutes are read as ‘opportunities’, which are taken up whether the successful applicant believes they will learn anything or not. There are those who are invested in approaching the space with openness, whereas for others being confronted with feminist theories this only opens the door for pre-existing ghosts (stereotypes, misogyny) to show up. The second challenge, which may also be viewed as an opportunity, is the ability to hold very lightly while firmly the importance of maintaining a teaching space where debate does not reproduce harmful and violent power relations. In describing a gender institute as informed by feminisms, this situates power and how it travels through violence as a disciplinary and regulatory technology. It challenges the dismissal of feminist scholarship as a tactic of erasure and refusal. Finally, it rejects the reproduction of violence in the form of debate and intellectual engagement even when having difficult and complex conversations. Consequently, for a gender institute the task is not about how you define yourself but the theoretical tools we choose to engage with and why. Futures and Transnational Intellectual Imperatives Over the years of their existence, the CODESRIA gender institutes have offered a methodological container in which to centre gender and advance what was contested in Engendering African Social Sciences[9] as missing in social sciences. I close with three observations about contemporary trends that require transdisciplinary, transnational work in future gender institutes. Battle of Ideas The ongoing threats to gender and feminist studies across the globe point to the threat posed by scholarship that challenges how we understand and organise the world. At the heart of the challenge to feminist and gender studies is a counter-hegemonic battle of ideas. Shaping this battle of ideas is the notion of ‘gender ideology’ as a coalescing framework. Early use of the term ‘gender ideology’ can be traced to the Vatican. Elizabeth Corredor[10] notes: In 2001, Pope John Paul II declared that ‘misleading concepts concerning sexuality and the dignity and mission of the woman’ are driven by ‘specific ideologies on “gender.”’ In 2002, the Vatican’s Pontifical Council for the Family asserted that a ‘feminist ideology . . . known as gender’ has led to a misunderstanding of the complementary difference between man and woman and ‘a growing confusion about sexual identity’ that ‘complicates the assumption of roles and the sharing of tasks in the home.’ The convergence between religious actors, such as the Catholic church, Christian fundamentalist groups and conservative secular actors, and political organising remains a critical concern for those interested in understanding how various actors mobilise to overturn hard-won freedoms. In addition, the use of formal political spaces—parliaments, political parties and legislation—as sites for this type of organising is equally critical. For example, US evangelical churches have supported anti-LGBTQI rhetoric through ‘training’ and financial resources. This strategy was evident in American evangelist Scott Lively’s role in the 2009 Bahati Bill[11] and, more recently, the role of groups such as Family WatchInternational[12] in the anti-homosexuality law Museveni assented to. Brazilian scholar Sonia Correa observes[13] the transcontinental nature of what she terms as a hydra, actively mobilising across Africa, Latin America,[14] Europe and North America. Brazil’s growing community of evangelical Christians[15] are now estimated to make up almost one-third of the country’s population of 215 million. Bolsonaro, the former Brazilian president whose campaign and political messaging railed against abortion, drugs, ‘gender ideology’, anti-Black rhetoric and communism, was backed by Brazilian evangelicals, with seven in ten backing him four years ago. There are varying degrees of political engagement and involvement among groups such as the Swedish Democrats, Danish People’s Party, Freedom Party of Austria and Alternative für Deutschland that could be viewed as fundamentalist politics. These degrees of distinction reflect the differences between the radical right and extreme right. Radical right groups are often hostile to liberal democracy but accept popular sovereignty and the minimal procedural rules of parliamentary democracy. Their support base is derived from challenging pluralism and targeting minority rights, but they publicly condemn the use of violence[16] as an instrument of politics. Extreme right organisations are often inspired by fascism or national socialism, tend to reject democracy and party politics, oppose all forms of ethnic and cultural diversity within the nation-state and are open to the use of violence to achieve political goals.[17] It is in these distinctions in political mobilisation that distinct battlegrounds emerge. Old Issues New Battles The place of citizenship defined broadly in the nation-state and globally, with gender, race and sexuality sitting at the heart of determining belonging, is a key feature of the battle of ideas. Most fundamentalist projects will opportunistically use anti-Western and anticolonial rhetoric as a basis for mobilisation. Within this mobilisation there are varying degrees of overlap between fundamentalism and ethnonationalism. A key feature of right-wing discourse is a return to a past and accompanying historical structures of dominance driven by the preservation of white supremacy and freedoms, which are perceived to be under threat from minorities. Within this narrative, historically marginalised groups are reimagined as powerful and a threat to white identity, thus necessitating a reaffirmation of what was historically dominant. The perceived threat from the imagined power of minorities allows the far right to mobilise a nationalist discourse to define difference and thereby exclusion. These discourses cut through the defence of the family, ‘gender ideology’, Islamophobia and homophobia, and the preservation of the ‘pure’ nation is often defined through an exclusion of those deemed as the ‘other’. By corralling moveable notions of ‘African culture’, ‘Christianity’ and ‘family values’, the spate of antihomosexuality laws across Africa mobilise very specific notions of heterosexuality designed to reconstitute a conservative interpretation of gender relations and roles. These laws respond to the unstable power that is attached to heterosexuality and vested in certain forms of dominant masculinities that are reliant on constructing womanhood in ways that sustain this. As Danai Mupotsa[18] argues: the success or failure of the project of ‘national culture’ (if we are to call it that) appears to be placed at the national family’s ability to manage and control the mobility and sexuality of women’s bodies, be it through mothers, fathers and brothers […]’ In addition, the accompanying ethnonationalist politics that shape political actors who mobilise a range of far-right ideologies is characterised by anti-Black and racist articulation of the ‘other’. Donald Trump and Jair Bolsanaro’s presidencies in the USA and Brazil, respectively, serve as examples of regimes that emboldened far-right groups, thus ramping up hate crimes associated with anti-immigrant and Islamophobic rhetoric, as seen in counter-movements such as White Lives Matter and the January 6th insurrection in the US capitol[19] by Trump supporters in 2021. Responses by various political regimes to questions that sit at the intersection of race, gender, sexuality and religious identity highlight how ‘panics’ often facilitate increasingly authoritarian measures for minorities. These panics have also arrived in universities through ‘academic freedom’. Across Africa, academics point to the constrained university environment within which they are to debate and teach complex contemporary issues. The question of academic freedom is not isolated to Africa, even if the nature of institutional autonomy differs greatly. The UK government has proposed a new law[20] to protect free speech and academic freedom, including appointing an academic freedom czar. The law places a duty on not only the university but also student unions to prevent discrimination against student faculty, staff or visiting speakers on their premises who hold views that are regarded as offensive. The law specifically sought to address concerns that right-wing actors are victims of silencing by left-wing activists on campuses. Saini notes[21] the recent growth in scientific racism framed as intellectual inquiry, which is seen in how this knowledge is rooted in science, repackaged as ‘fact’ and supported by data and peer-reviewed journals. By legitimising racist claims as ‘scientific’ they are then framed as indisputable and disseminated accordingly. Targeting counter-hegemonic scholarship is a deliberate strategy of curbing the growth of ideas that challenge systems of power. The increasing surveillance of universities by governments has the potential to severely paralyse institutional governance and threatens fields of study, such as feminist and gender studies, and the scholars invested in them. Transnational and Transdisciplinary Imperatives If, as illustrated above, the stakes in protecting and sustaining gender studies are high, then the task of future CODESRIA gender institutes becomes even greater in three ways. The first task is in both elevating and strengthening the feminist underpinnings of the gender institutes, including insisting on adjacent institutes—such as the governance institute—taking feminist scholarship seriously as part of an inter- and transdisciplinary commitment. In elevating the feminist logics that shape how we understand the utility of gender in governing the world, the institutes must seriously consider the material realities of women in Africa while not retreating to an essentialist and instrumentalist understanding of women and gender. To focus solely on the victimhood of women and girls is to ignore what feminist scholarship demands of us, which is to explore how gender roles and relations came to be rather than a focus on what gender relations are. The second task is the pedagogical expectations we place on the institute as a methodology for meaning- and change-making. If, as observed earlier on, the institutes play a critical role in building feminist epistemic communities, then the pedagogical demands on the institutes from those who resource them as teachers and those who attend the institutes becomes greater. The institute moves from being yet another ‘opportunity’ for training and potentially being published to a space that embraces its role in the development of counter-hegemonic knowledge[22]. The third task concerns the role of knowledge production, particularly the research outputs that emerge from the gender institutes. Here I return to the question of ethical citation practices and an accompanying demand for effective and productive engagement with African feminist scholarship specifically and feminist scholarship generally [1] Zeleza, P., 2018, The Giant Challenge of Higher Education in Africa, The Elephant, 5 July. https://www.theelephant.info/features/2018/07/05/the-giant-challenge-of-higher-education-in-africa/ [2] Kowaltowski, A., Oliviera, M., Silber, A. and Chaimovich, H., 2021, The push for open access is making science less inclusive, Times Higher Education, 31 August. https://www.timeshighereducation.com/opinion/push-open-access-making-science-less-inclusive [3] Open Letter to African Studies Review Journal Editorial Board: Call for Retraction of Article 'African Studies Keyword: Autoethnography'https://docs.google.com/forms/d/e/1FAIpQLSdKo9OgNuU0DcYMBRbuTvv2wu-sJE3StYIIaFuclGJiDevx8g/viewform?pli=1 [4] African Studies Review, 26 June 2022. https://africanstudies.org/wp-content/uploads/2017/08/ASR-Response-6.26.22.pdf [5] Redden, E., 2018, Global Attack on Gender Studies, Inside HigherEd, 5 December. https://www.insidehighered.com/news/2018/12/05/gender-studies-scholars-say-field-coming-under-attack-many-countries-around-globe [6] Medie, P. A., and Kang, A. J., 2018, ‘Power, knowledge and the politics of gender in the Global South’, European Journal of Politics and Gender, Vol. 1, Nos. 1-2, pp. 37-54, available from: https://doi.org/10.1332/251510818X15272520831157> Accessed 5 July 2023. [7] Mikdashi, M., 2012, How Not to Study Gender in the Middle East, Jadaliyya 21 March. https://www.jadaliyya.com/Details/25434 [8] Oyewumi, O., 1997, The Invention of Women: Making an African Sense of Western Gender Discourses, Minneapolis, MI: University of Minnesota Press. [9] Imam, A., Mama, A. and Sow, F., eds. 1997, Engendering African Social Sciences, Dakar: CODESRIA. https://www.africanbookscollective.com/books/engendering-african-social-sciences [10] Corredor, E., 2019, Unpacking ‘Gender Ideology’ and the Global Right’s Antigender Countermovement, Signs: Journal of Women and Culture in Society, Vol. 44, No. 3. https://www.journals.uchicago.edu/doi/abs/10.1086/701171?mobileUi=0& [11] Center for Constitutional Rights, 11 October, 2019, Sexual Minorities Uganda v. Scott Lively, https://ccrjustice.org/home/what-we-do/our-cases/sexual-minorities-uganda-v-scott-lively [12] Wepukhulu, K. S. 2023, Calls for US anti-rights groups to face action over Uganda anti-gay law,O pen Democracy, 5 May. https://www.opendemocracy.net/en/5050/uganda-anti-gay-law-sharon-slater-tim-kreutter/ [13] Correa, S., 2017, Gender Ideology: tracking its origins and meanings in current gender politics, LSE, 11 December. https://blogs.lse.ac.uk/gender/2017/12/11/gender-ideology-tracking-its-origins-and-meanings-in-current-gender-politics/ [14] Carbajal, M., 2022, How trans rights are being ‘weaponised’ by Latin American right-wing populists, Open Democracy, 29 August. https://www.opendemocracy.net/en/5050/trans-rights-lgbt-latin-america-brazil-bolsonaro/ [15] Garcia, R. T., 2022, Evangelicals in Brazil are stronger today than ever before, Al-Jazeera, 7 January.https://www.aljazeera.com/opinions/2022/1/7/evangelicals-in-brazil-are-stronger-today-than-ever-before [16] Ravndal, J. A. and Enstad, J. D., 2021, What Explains Far-Right Violence?, University of Oslo, 14 March, https://www.sv.uio.no/c-rex/english/groups/compendium/what-explains-far-right-violence.html [17] Gattinara, P. C., Leidig, E. and Ravndal, J. A., 2023, What characterizes the far right scene in Europe and beyond? University of Oslo, 5 July.https://www.sv.uio.no/c-rex/english/groups/compendium/what-characterizes-the-far-right-scene-in-Europe-and-beyond.html#_ftn19 [18] Mupotsa, D., 2019, This Little Rage of Poetry: Researching Gender and Sexuality, Feminist Africa, https://feministafrica.net/wp-content/uploads/2019/10/fa_11_9_standpoint_2.pdf [19] AP News, 23 July 2022, From ‘an attempted coup’ to chaos, searing moments of Jan. 6. https://apnews.com/article/jan-6-hearings-key-moments-b374e48ab5a1a0a597fd5b6ec69048c2 [20] UK Department of Education, 2021, Higher Education: free speech and academic freedom. https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/961537/Higher_education_free_speech_and_academic_freedom__web_version_.pdf [21] Jha, A., 2019, Superior: The return of race science by Angela Saini, The Guardian, 27 May, https://www.theguardian.com/books/2019/may/27/superior-the-return-of-race-science-by-angela-saini-book-review [22] Shivji, I. 2019, Social responsibility of intellectuals in building counter-hegemonies, Pambazuka News, 10 February. https://www.pambazuka.org/pan-africanism/social-responsibility-intellectuals-building-counter-hegemonies